Vortex pinning properties in Fe-chalcogenides. (14th October 2015) - Leo, A; Grimaldi, G; Guarino, A; Avitabile, F; Nigro, A; Galluzzi, A; Mancusi, D; Polichetti, M; Pace, S; Buchkov, K; Nazarova, E; Kawale, S; et al.
Abstract: Among the families of iron-based superconductors, the 11-family is one of the most attractive for high field applications at low temperatures. Optimization of the fabrication processes for bulk, crystalline and/or thin film samples is the first step in producing wires and/or tapes for practical high power conductors. Here we present the results of a comparative study of pinning properties in iron-chalcogenides, investigating the flux pinning mechanisms in optimized Fe(Se Te x ) and FeSe samples by current–voltage characterization, magneto-resistance and magnetization measurements. In particular, from Arrhenius plots in magnetic fields up to 9 T, the activation energy is derived as a function of the magnetic field, whereas the activation energy as a function of temperature, is derived from relaxation magnetization curves. The high pinning energies, high upper critical field versus temperature slopes near critical temperatures, and highly isotropic pinning properties make iron-chalcogenide superconductors a technological material which could be a real competitor to cuprate high temperature superconductors for high field applications.